Uma análise freireana sobre a formação do sujeito pela prática de ensino realizada no laboratório de direitos humanos do movimento popular práxis de Tatuí –SP - Arruda, Graci Marieli Vieira de (Universidade Federal de São Carlos, 2021)
The present work aims to contribute to a Freire analysis on the practice of non-school teaching of a revolutionary leadership in the face of the category of authentic praxis, starting from a concrete reality. This is a qualitative research that discusses the theme from a Freirean perspective, the object of study is the Human Rights Laboratory (LDH) of the Popular Praxis Movement, specifically in relation to the practice of non-school teaching. The proposed objective is to investigate the subjects' formative practice before the category of authentic praxis and for that the theoretical foundation was based on Paulo Freire, Karl Marx, Enrique Dussel, Sergio Lessa and Ivo Tonet. The main concern of this research is summarized in the following question: To what extent does the LDH group practice implemented by this Social Movement adopt Freirien parameters to carry out the formation of the subject? Material was collected for analysis by the Popular Praxis Movement, participant observation during the meetings of the Human Rights Laboratory, semi-structured interviews and case study. The process of choosing the analysis category was based on the works of Paulo Freire, linked to some concepts of Marxist thought. The analysis made us see that the LDH carries out a teaching practice based on the category of authentic praxis according to Freirean parameters during the process of dialogue construction, in which there is an exchange of knowledge between the union of theory and practice, resulting in a collective development of awareness and future actions to overcome the contradiction denounced through the dialogue carried out during the meetings.
A freirean analysis on the formation of the subject by the teaching practice performed at the human rights laboratory of the popular movement práxis de Tatuí –SP
Keywords: Práxis autêntica, conceitos marxistas e formação do sujeito; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO